Enhancing Students’ Nationalist Attitudes Through the Numbered Heads Together Model in Grade 4 Civic Education Lessons - Amelia Dwi Astuti; Khaidir Fadil Fadil; Hambari (STKIP Al Islam Tunas Bangsa dan HEPI, 2026)
This study was motivated by the low level of nationalism among fourth-grade students at SDN Cimanggu in Bogor City in the subject of Civic Education (PKn). The purpose of this study was to determine the improvement in students’ nationalistic attitudes through the application of the Numbered Heads Together (NHT) learning model. The method used was Classroom Action Research (CAR) with two cycles. The research subjects were 30 fourth-grade students. Data collection was conducted using a nationalism attitude questionnaire and an observation sheet for teacher and student activities. The results showed a significant improvement: in the pre-cycle, the average student score was 66 (fair category), increasing to 74 in Cycle I (good category), and reaching 91 in Cycle II (very good category). Teacher activities also improved from a score of 78 in Cycle I to 88 in Cycle II. It was concluded that the NHT learning model proved effective in improving students’ nationalistic attitudes, particularly in the aspects of cooperation, responsibility, and the courage to express opinions